STUDENTS' GAMMA SUBSCRIPTION RENEWAL INTENTION: CUSTOMER EXPERIENCE, PERCEIVED VALUE, AND EASE OF USE - Wenti Ayu Sunarjo; Siti Nurhayati; Hauro Insiyyah (PT. Berkah Digital Teknologi, 2026)
Purpose: This study examines whether customer experience, perceived value, and perceived ease of use explain students’ intention to renew their Gamma subscriptions. Research Methodology: A cross-sectional explanatory survey was conducted with 100 active Universitas Pekalongan students who identified themselves as current or former Gamma subscribers. Respondents were selected through purposive sampling, and the data were analyzed using IBM SPSS Statistics through item-total validity tests, Cronbach’s alpha, classical regression diagnostics, analysis of variance, and multiple linear regression. Results: The model was significant, F (3, 96) = 58.657, p < .001, and explained 64.7% of the variance in subscription renewal intention (adjusted R² = .636). Customer experience (B = .266, β = .271, p = .004), perceived value (B = .474, β = .400, p < .001), and perceived ease of use (B = .213, β = .221, p = .027) were positive predictors. Perceived value showed the largest standardized association. Limitations: The cross-sectional, single-institution, self-report design limits causal inference and external validity. The perceived-value scale also showed only marginal internal consistency (α = .630). Contribution: The study extends post-adoption research to a visual generative-AI subscription context and identifies value delivery, experience quality, and low interaction effort as relevant retention considerations for student-oriented software-as-a-service providers.